Efecto de barreras alelopáticas y biocidas en el manejo de insectos plagas del cultivo de pimiento (Capsicum annuum). - Yánez Vera, Viviana Gabriela (2016)
The objective of the present investigation was to evaluate the use of allelopathic and biocidal barriers in pest management of the pepper crop. The trial was carried out in the farm "Verdesoto" located in the Km 8.5 of the road El Empalme - La Guayas, belonging to that canton. Due to the characteristics of the test and the difficulty of blocking, it used a 2x3 Divide Parcel design in 3 replicates, the main plots (factor A) being the allelopathic barriers of rue and basil, and the subplots (factor B) Tobacco, neem and oregano, which combination produced 6 interactions. As main results, we found evidence that the height variables of plants at 45 and 60 days of cultivation age, days at flowering, number of fruits per plant, diameter, length and weight of fruits were not influenced by the barriers, Biocides and combinations between the factors, an exception of the combination of rue bar with the neon biocide that produces the fruits of greater weight, surpassing between 11.9 and 42.9% to the weight of the fruits registered with the other interactions. The yield obtained with the superior quality barrier only by 0.3% to the yield obtained with the basil barrier, and a control of trips and white fly by 17.4 and 35.0% more than the basil barrier, Respectively, while the Basil Barrier controlled aphids at 4.2% more than the ruda barrier. The tobacco biocide produced a yield of 11.1 and 15.8% above the yields obtained with the neem and oregano biocides, respectively, and in turn demonstrated a control of trips, aphids and whitefly of 73.9, 14.0 and 52.2% above the neem biocide, respectively, and in turn exceeded the biocide of oregano by 233.3, 42.5 and 191.7%. By using the combination of the basil barrier with the oregano biocide, the highest yield per hectare was obtained in the present study. 31.5% to the results obtained by the other combinations of allelopathic barriers and biocides. The combination of the rude barrier and the use of the tobacco biocide recorded a control of travel ranging from 87.0 to 330.0%, and of the whitefly between 33.3 and 300.0%, with respect to the other combinations under study. By combining the basil barrier with the spray of the tobacco biocide, reducing from 13.2 to 50.0% the incidence of aphids. Keywords: pepper, allelopathy, biocides